Vital Signs During the COVID-19 Outbreak: A Retrospective Analysis of 19,960 Participants in Wuhan and Four Nearby Capital Cities in China - Jing-Wei Li; Yu-Tao Guo; Gian Luca Di Tanna; Bruce Neal; Yun-Dai Chen; Aletta E. Schutte (Ubiquity Press, 2021)
Background: The implications of city lockdown on vital signs during the COVID-19 outbreak are unknown. Objective: We longitudinally tracked vital signs using data from wearable sensors and determined associations with anxiety and depression. Methods: We selected all participants in the HUAWEI Heart Study from Wuhan and four nearby large provincial capital cities (Guangzhou, Chongqing, Hangzhou, Zhengzhou) and extracted all data from 26 December 2019 (one month before city lockdown) to 21 February 2020. Sleep duration and quality, daily steps, oxygen saturation and heart rate were collected on a daily basis. We compared the vital signs before and after the lockdown using segmented regression analysis of the interrupted time series. The depression and anxiety cases were defined as scores ≥8 on the Hospital Anxiety and Depression Scale depression and anxiety subscales [HADS-D and HADS-A] in 727 participants who finished the survey. Results: We included 19,960 participants (mean age 36 yrs, 90% men). Compared with pre-lockdown, resting heart rate dropped immediately by 1.1 bpm after city lockdown (95% confidence interval [CI]: -1.8, -0.4). Sleep duration increased by 0.5 hour (95% CI: 0.3, 0.8) but deep sleep ratio decreased by 0.9% (95% CI: -1.2, -0.6). Daily steps decreased by 3352 steps (95% CI: -4333, -2370). Anxiety and depression existed in 26% and 17% among 727 available participants, respectively, and associated with longer sleep duration (0.2 and 0.1 hour, both p < 0.001). Conclusions: Lockdown of Wuhan in China was associated with an adverse vital signs profile (reduced physical activity, heart rate, and sleep quality, but increased sleep duration). Wearable devices in combination with mobile-based apps may be useful to monitor both physical and mental health. Clinical trial registration: The trial is registered at Chinese Clinical Trial Registry (ChiCTR) website (ChiCTR-OOC-17014138).